Ingestion itérative d’objets ferromagnétique : urgence digestive potentiellement catastrophique - KABAS Raïssa-Michelle; KOUAO Jean-Paul Stephens; MEITE Mamonma; BAKHTRI Malek; DIABATE Aboubakar Sidiki; Wallid Zarrhedinne (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
Multiple magnets ingestion or simultaneous ingestion of a magnet with a metallic foreign body can lead to serious and potentially life-threatening complications. Imaging plays a crucial role in the treatment decisions by early detection of these complications, thus leading to appropriate surgical intervention, particularly by laparoscopy or laparotomy in order to carry out the most comprehensive assessment possible for efficient and effective management. We present the case of a 12-year-old girl who accidentally ingested, repeatedly, multiples small ferromagnetic foreign body causing occlusion with peritonitis, diagnosed by computed tomography (CT) and resulting in extensive intestinal resection.